2005
DOI: 10.1088/1126-6708/2005/02/065
|View full text |Cite
|
Sign up to set email alerts
|

Strings in a 2-d Extremal Black Hole

Abstract: String theory on 2-d charged black holes corresponding to SL(2)×U(1) L U(1)exact asymmetric quotient CFTs are investigated. These backgrounds can be embedded, in particular, in a two dimensional heterotic string. In the extremal case, the quotient CFT description captures the near horizon physics, and is equivalent to strings in AdS 2 with a gauge field. Such string vacua possess an infinite space-time Virasoro symmetry, and hence enhancement of global space-time Lie symmetries to affine symmetries, in agreeme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 60 publications
(134 reference statements)
0
42
0
Order By: Relevance
“…Since extremal black holes have an AdS 2 factor in their near horizon geometry [7,8], one expects that the underlying quantum gravity theory in this background will have a dual description in terms of a conformal quantum mechanics (CQM) living at the boundary of AdS 2 [9][10][11][12][13][14][15][16][17][18][19][20]. In [19] it was shown that in the classical limit, when Wald's formula is expected to be valid, the Wald entropy computed from the entropy function can be interpreted as the logarithm of the ground state degeneracy of this dual CQM in a fixed charge sector.…”
Section: Jhep04(2009)034mentioning
confidence: 99%
See 1 more Smart Citation
“…Since extremal black holes have an AdS 2 factor in their near horizon geometry [7,8], one expects that the underlying quantum gravity theory in this background will have a dual description in terms of a conformal quantum mechanics (CQM) living at the boundary of AdS 2 [9][10][11][12][13][14][15][16][17][18][19][20]. In [19] it was shown that in the classical limit, when Wald's formula is expected to be valid, the Wald entropy computed from the entropy function can be interpreted as the logarithm of the ground state degeneracy of this dual CQM in a fixed charge sector.…”
Section: Jhep04(2009)034mentioning
confidence: 99%
“…However in that paper the authors interpreted the φ coordinate as the euclidean time direction and the u coordinate as the spatial circle, thereby arriving at a modular transformed version of eq. (16). Since our goal is to identify the CQM living on the boundary of AdS 2 , we must choose u as the time coordinate on the boundary of AdS 3 so that it matches the time coordinate of the CQM.…”
Section: Jhep04(2009)034mentioning
confidence: 99%
“…can be constructed as follows (see [10] for a recent discussion). We start with the supersymmetric SL(2, IR) WZW model at level k, whose central charge is c =c = 3 + 6 k + 3 2 , and add to it a left-moving supersymmetric U (1) current with c = In the coset description, the maximal extension of the background (2.1) -(2.3) splits into different regions, each of which is described by its own set of natural coordinates.…”
Section: Lorentzian Black Holementioning
confidence: 99%
“…k 0 is determined by the length of the vector (3.9), 10) and the mass-shell condition for the tachyon,…”
Section: Reissner-nordstrom Black Holesmentioning
confidence: 99%
“…The metric of the two-dimensional charged black hole [23] with mass M and charge q in suitable coordinates can be written as [26,27]…”
Section: Thermodynamics Of the Charged Black Holementioning
confidence: 99%